2003
DOI: 10.1046/j.1365-2850.2003.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of collaboration inpatient treatment between the community psychiatric health services and a psychiatric hospital in Norway

Abstract: The aim of this study was to examine factors that may have an influence on the collaboration between the health-care professionals in a psychiatric hospital and two communities' psychiatric health service departments. Interviews were conducted with three psychiatric nurses, one medical practitioner, one health and social manager and one cultural worker; thus a total of nine informants. The transcribed interview texts were analysed by means of qualitative content analysis. The main results showed that the commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…They presented several examples of how they collaborated in individual cases and pointed out the need for more systematic collaboration. This is in accordance with Holst and Severinsson [7], who found that collaboration between the municipality and hospital took the form of ad hoc meetings. The respondents underlined the need for more structured professional guidelines and collaboration in order to improve the quality of CMHC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They presented several examples of how they collaborated in individual cases and pointed out the need for more systematic collaboration. This is in accordance with Holst and Severinsson [7], who found that collaboration between the municipality and hospital took the form of ad hoc meetings. The respondents underlined the need for more structured professional guidelines and collaboration in order to improve the quality of CMHC.…”
Section: Discussionsupporting
confidence: 91%
“…However, their dialogues also revealed and made them more aware of the differences between them. Meeting at a monthly forum provided an opportunity to facilitate a common understanding of their different skills, which is supported by [7]. The two teams developed a greater awareness of different types of knowledge, such as their own experiential knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means communication and passing on information between staff from PC and social service is mainly based on values and experiences of the staff involved. Similarly, Holst and Severinsson (18) illuminate the importance of a more systematic interdisciplinary collaboration that may facilitate common understanding of different skills among the professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Research is mostly UK‐based but increasing in other countries (e.g. Holst & Severinsson 2003, Wallace et al. 2005, Bellali & Kalafati 2006, Elsom et al.…”
Section: Introductionmentioning
confidence: 99%